PEMIKIRAN GRAMATIKAL AL-SIBAWAIH: TELAAH HISTORIS, METODOLOGIS, DAN IMPLIKASINYA TERHADAP LINGUISTIK ARAB KONTEMPORER - Zetarihana Fadla Fachrina; Inka Maulidi Haery; Kamilatun Nazilla; Fajar Nur Zahrah (Jurnal Sathar, 2025)
This study aims to examine the grammatical thought of al-Sibawaih through a historical and methodological approach, as well as to analyze its implications for the development of contemporary Arabic linguistics. Al-Sibawaih is a central figure in the codification of Arabic grammar through his monumental work, Al-Kitāb, which remains a primary reference in the study of Arabic grammar to this day. This research employs a descriptive qualitative method based on library research, using content analysis techniques on classical texts and relevant secondary sources. The findings reveal that al-Sibawaih’s methodology is systematic and rational, emphasizing linguistic logic through theories such as ‘āmil, ma‘mūl, and qiyās. His contributions not only laid the foundational framework of classical Arabic grammar but also significantly influenced the direction of modern Arabic linguistics in both theoretical and pedagogical aspects. His visionary ideas remain relevant and serve as a bridge between classical linguistic heritage and contemporary, contextualized linguistic approaches.